Visceral leishmaniasis in border areas : clustered distribution of phlebotomine sand flies in Clorinda, Argentina - Salomón, Oscar Daniel (2009)
Fil: Salomón, Oscar Daniel. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.